Duocrassana longula, new genus and species of leafhopper (Hemiptera: Cicadellidae: Deltocephalinae) from southern Mexico and its relationship to other genera in Athysanini - Pinedo-Escatel, J. A.; Zahniser, J. N; Dietrich, C. H.; Moya-Raygoza, G. (Zootaxa, 2016)
The new leafhopper genus, Duocrassana Pinedo-Escatel, Zahniser & Dietrich, gen. nov., and its type species, Duocrassana longula Pinedo-Escatel, Zahniser & Dietrich sp. nov., are described and illustrated based on material from Oaxaca, Mexico. The relationship with other genera in the tribe Athysanini is discussed, highlighting the importance of male genitalia for its identification.